Diversité et caractéristiques des crabes de lagunes au Sud-Bénin, Afrique de l'Ouest - DESSOUASSI, Comlan Eugène; Lederoun, Djiman; CHIKOU, ANTOINE; LALEYE, PHILIPPE A. (My University, 2018)
The article focuses on crab’s diversity in Benin’s lagoons. An inventory was conducted from february 2017 to january 2018. The crabs were sampled from the artisanal fishing and experimental catches. Fourteen crabs species belonging to twelve genera and six families were identified. The Portunidae family is the most represented with six species followed by Sesarmidae family with three species and two species for Ocypodidae family. The families of Gecarcinidae, Grapsidae and Panopeidae are each represented by a species. Callinectes pallidus, Cronius ruber, Ocypode cursor, Chiromantes angolensis and Charybdis hellerii have been reported for the first time in Benin lagoons. Charybdis hellerii is an indo-Pacific invasive species. An ecological monitoring of this invasive species is required on the West African coast.
Keywords: diversité; crabes; Bénin; Charybdis hellerii